Development and Initial Validation of the Refugee Health Literacy Assessment Tool (RHLAT). Issue 6 (2nd November 2021) - Harris, Megan A.; Colvin, Kimberly F.; Lindner, Nora E.; Manganello, Jennifer A.; Mohamed, Liban; Shaw, Andrea V.
ABSTRACT: Background: Culturally and linguistically diverse (CALD) refugees and immigrants in the United States (U.S.) face barriers to accessing health care, and are more likely to have worse health outcomes as it relates to chronic disease. Better understanding health literacy for this population can identify gaps in knowledge, facilitate health education, and improve health outcomes. Purpose: The Refugee Health Literacy Assessment Tool (RHLAT) was developed to improve patient-centered chronic disease management by identifying aspects of health literacy for which individual refugees require additional support. Methods: RHLAT development involved domain identification, item development, expert reviews, and cognitive interviews. Refugee and immigrant patients with uncontrolled diabetes and cardiovascular risk factors were engaged for RHLAT implementation. Results: The tool was valid across different types of interpretation, such as in-person interpreter or over the phone, and revealed a wide range of health literacy in this population. Discussion: The RHLAT was developed and tested with a CALD refugee population. The tool revealed gaps in health literacy that could be addressed by the care team. Translation to Health Education Practice : This study provides a tool that can be used in practice to identify areas for additional health education to assist CALD patients in navigating the U.S. healthcare system.